Optimal stochastic operation of technical virtual power plants in reconfigurable distribution networks considering contingencies - Aghdam, Farid Hamzeh; Javadi, Mohammad Sadegh; Catalão, João P.S. (International journal of electrical power & energy systems, 2023)
Virtual Power Plants (VPPs) are one of the concepts introduced in modern power systems to handle the increasing number of the distributed generation (DG) units. Technical VPPs (TVPPs) consider both financial and technical perspectives of using DGs in the system. Besides, secure and reliable operation of the system is a priority. In this paper, optimal operation of technical virtual power plants in a reconfigurable network is formulated as an optimization problem to resolve the probable contingency problem in the lines of the system. The VPP is assumed to be a multi-carrier energy system including combined heat and power (CHP), renewable DGs and dispatchable DGs beside thermal and electrical storage systems and loads. The uncertainties of renewable based DGs and demand levels are handled using chance constrained programming (CCP). By using CCP in presence of uncertain parameters, the security of the system can be guaranteed in predefined level of probability. Finally, to evaluate the effectiveness, quality and applicability of the proposed methodology, the problem is structured as a mixed-integer nonlinear programming (MINLP) problem which is solved using General Algebraic Modeling System (GAMS) software via Baron solver. •Proposing an optimal scheduling for TVPP trying to resolve contingency problem.•Considering a VPP with variety of energy systems.•Considering the uncertainties of wind, photovoltaic units and loads.•Modeling the uncertainties via chance constrained programming (CCP).